Vam3, a Compound Derived from Vitis amurensis Rupr., Attenuated Colitis-Related Tumorigenesis by Inhibiting NF-κB Signaling Pathway - Xuan, Lingling; Jiang, Rentao; Wu, Zhiyuan; Yi, Honggan; Yao, Chunsuo; Hou, Qi; Qu, Chunfeng (Frontiers in Pharmacology, 2016)
Background: Chronic inflammation is one of the important mediators of colitis-related colon cancer (CRC). Abundant mast cells (MCs) were observed in the tumor microenvironment and mediators released upon MC activation play an important role in the process of chronic inflammation. Previously, we found that activation of intestine mucosal MCs recruited and modulated the inflammatory CD11b+Gr1+ cells to promote the CRC development. In the current study we investigated the effects of Vam3, a resveratrol dimer with potent anti-inflammatory effects, on CRC development. Methods: RBL-2H3 cells, a basophilic leukemia cell line, were pretreated with 2.5 or 5 μΜ Vam3 and then stimulated with dinitrophenol-conjugated bovine serum albumin (DNP-BSA) plus lipopolysaccharide (LPS). The MC degranulation was determined by measuring β-hexosaminidase release. Generation of TNF-α and IL-6 in RBL-2H3 cells or in peritoneal macrophages was determined by ELISA and real-time qPCR. NF-κB p65 and phospho-NF-κB p65 expression was determined by Western blotting. NF-κB activity in RAW264.7 cells was determined by luciferase reporter assay. CRC was induced in C57BL/6 mice by intraperitoneal injection of azoxymethane (AOM), followed by oral exposure to dextran sodium sulfate (DSS). Vam3 at 50 mg/kg, or disodium cromoglycate (DSCG, MC stabilizer) at 100 mg/kg, or vehicle were administrated to the mice 4 weeks after DSS withdrawal. Levels of TNF-α, IL-6, and mouse MC protease-1 were determined by ELISA. Infiltration of CD11b+Gr1+ cells was determined by flow cytometry analysis. One-way ANOVA was used to compare difference between groups. Results: Pretreatment with Vam3 significantly inhibited RBL-2H3 cell degranulation and inflammatory cytokine production from RBL-2H3 cells and from peritoneal macrophages. After Vam3 treatment, NF-κB activity in RAW264.7 cells, and expressions of phospho-NF-κB p65 in RBL-2H3 cells and in peritoneal macrophages were significantly down-regulated. In the AOM plus DSS-induced CRC murine model, the Vam3 and DSCG-treated mice had less tumor numbers than those treated with vehicle. Expression of phospho-NF-κB p65, production of inflammatory cytokines, and infiltration of MCs and CD11b+Gr1+ cells were attenuated in the Vam3-treated mice. Conclusions: Vam3 treatment could attenuate the CRC development. This effect may be due to its inhibition on NF-κB signaling pathway in MCs and macrophages of the inflamed intestines.